A coupled consolidation shear model for the process of formation of glaciated soils - Huang, Bingquan; Sharma, Jitendra S. (Canadian Geotechnical Journal, 2008)
It has been generally observed that the measured preconsolidation pressure values for glaciated soils are not compatible with the measured effective pressure values at the bed of the glacier if one-dimensional consolidation alone is considered as the formation process for these soils. In this paper, a new model for the process of formation of glaciated soil, termed the coupled consolidation shear (CCS) model, is developed using the frameworks of critical state soil mechanics and small-strain consolidation theory. The CCS model includes simultaneous shearing and consolidation of subglacial sediments and is able to simulate profiles of preconsolidation pressure versus depth that closely resemble those observed in glaciated soils. The CCS model is validated by successfully simulating the profile of preconsolidation pressure versus depth for an 80 m deep Battleford till layer in Birsay, Saskatchewan, Canada. The CCS model suggests the existence of anisotropic yield strength and stiffness in glaciated soils as a consequence of coupling subglacial shear and consolidation.